(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
Conceived in the 1960s, a period of great economic and social transformations in Brazil, Folkcommunication was born with the aim of overcoming Communication problems by seeing and understanding the reactions of a people who lived on the margins, without any engagement with the media. In this same period, the coupling of “communication” and “development” seeks a public atmosphere favorable to social transformation in Latin America. Considering that the two theoretical approaches complement each other, this work proposes a crossing between Folkcommunication and Communication for Development (C4D), based on a literature review. The contribution of this research is based on the recognition of folkcommunication within the perspective of social development and on the appreciation of the dialogue between the two aspects.